Using data to support evidence-informed decisions about skilled birth attendants in fragile contexts: a situational analysis from Democratic Republic of the Congo - Amuda Baba; Tim Martineau; Sally Theobald; Paluku Sabuni; Joanna Raven (BMC, 2020)
Abstract Background Most low- and middle-income countries are experiencing challenges in maternal health in relation to accessing skilled birth attendants (SBA). The first step in addressing this problem is understanding the current situation. We aimed to understand SBA's availability and distribution in Ituri Province, North Eastern Democratic Republic of the Congo (DRC) from 2013 to 2017. Methods We used available data on SBAs (doctors, nurses and midwives) from the Ituri Provincial Human Resource for Health Management Unit's database from 2013 to 2017. The current distribution across and within three categories of district (rural, peri-urban and urban) and characteristics of SBAs as well as 5-year trends and vacancy trends were identified. Data on training outputs for SBA cadres was collected from training schools in the province. Descriptive analysis, disaggregating by district, cadre and gender where possible, was conducted using Excel. Results The national ratio of SBAs per 1000 population is four times less than the Sustainable Development Goals threshold (4.45) while the Ituri Province ratio is one of the lowest in DRC. There are more doctors and nurses in urban and peri-urban districts compared to posts, and shortages of midwives in all district categories, particularly in rural districts. From 2013 to 2017, occupied posts for doctors and nurses in all three categories of districts increase while midwives decrease in peri-urban and rural districts. There is clear gender and occupational segregation: doctors and nurses are more likely to be male, whereas midwives are more likely to be female. The projections of training outputs show a surplus against authorised posts of doctors and nursing increasing, while the shortfall for midwives remains above 75%. Conclusion This is the first study to use existing human resource data to analyse availability and distribution of SBAs in a DRC province. This has provided insight into the mismatch of supply and demand of SBAs, highlighting the extreme shortage of midwives throughout the province. Further investigations are needed to better understand the situation and develop strategies to ensure a more equitable distribution of SBAs throughout this province and beyond. Without this, DRC will continue to struggle to reduce maternal mortality.